The role of vitamin D in reducing gastrointestinal disease risk and assessment of individual dietary intake needs: Focus on genetic and genomic technologies. Issue 1 (28th August 2015) - Ferguson, Lynnette R.; Laing, Bobbi; Marlow, Gareth; Bishop, Karen
Abstract : With the endogenous formation of vitamin D being significantly curtailed because of public awareness of skin cancer dangers, attention is turning to dietary sources. Cumulative evidence has implicated vitamin D deficiency in increasing susceptibility to various gastrointestinal disorders, including colorectal cancer, inflammatory bowel diseases, diverticulitis, and irritable bowel syndrome. There is also reason to suggest adjunct vitamin D therapy for such diseases. Although there is justification for increasing vitamin D intake overall, optimal intakes will vary among individuals. Genomic technologies have revealed several hundreds of genes associated with vitamin D actions. The nature of these genes emphasizes the potentially negative implications of modulating vitamin D intakes in the absence of complementary human genetic and genomic data, including information on the gut microbiome. However, we are not yet in a position to apply this information. Genomic data (transcriptomics, metabolomics, proteomics, and metagenomics) could provide evidence that vitamin D sufficiency has been achieved. We suggest that there is an increasingly strong case for considering the more widespread use of vitamin D fortified foods and/or dietary supplements to benefit gastrointestinal health. However, intake levels might beneficially be informed by personalized genetic and genomic information, for optimal disease prevention and maintenance of remission.